Hooked : a novel of obsession - Yuzuki, Asako, 1981- (Ecco, an imprint of Harper Collins Publishers, 2026)
"Eriko's life looks perfect--from her prestigious job at a Japanese trading firm to her spotless apartment and devoted parents. Her newest project, to reintroduce the controversial Nile Perch into the Japanese market, is as ambitious as she is. But beneath her flawless surface lies a consuming loneliness. Eriko has never been able to hold on to a real friend. Enter Shoko: a popular lifestyle blogger whose work Eriko follows obsessively. Shoko lives a life of controlled chaos--messy apartment, take-out dinners, a kind, easy-going husband. She writes about daily contentment, though her fractured relationship with her father gnaws at the edges of her happiness. When Eriko orchestrates a "chance" meeting with Shoko, the two women strike upan unlikely connection. For a fleeting moment, Eriko believes she'sfinally found what she's always longed for. But as her fascination turns to fixation and Shoko's carefully balanced life begins to dissolve, both women are pushed to breaking points neither of them saw coming."--Provided by publisher.